Epidemiology, Diagnostics and Therapy of Vulvovaginal Fungal Infections - Magdalena Frej-Mądrzak; Agnieszka Jama-Kmiecik; Aleksandra Górzyńska; Nikola Wahdan; Urszula Nawrot (Pathogens, 2026)
Vulvovaginal candidiasis (VVC) is one of the most common superficial fungal infections affecting women. A particularly challenging issue is the treatment of recurrent vulvovaginal candidiasis (RVVC)—defined as ≥4 episodes of VVC within 12 months—which affects 5–8% of women with VVC. The development of VVC is influenced by many risk factors related to the host organism and behaviour, including disturbances in the vaginal microflora, hormonal fluctuations, diabetes, hygiene and sexual behaviour. Although C. albicans remains the primary species causing this infection, infections caused by other species, such as Nakaseomyces glabratus and Pichia kudriavzevii, are becoming increasingly common, partly due to the widespread use of azole antifungal drugs and growing drug resistance. Therefore, this publication focuses on a review of the newest literature concerning the epidemiology, diagnosis, current approaches to antifungal susceptibility testing and treatment according to global guidelines. According to the literature, precise species identification and drug susceptibility testing are crucial to avoid therapeutic errors and drug resistance. Moreover, new antifungal drugs such as tetrazoles (oteseconazole) and triterpenoids (ibrexafungerp) are entering clinical practice, offering high efficacy against resistant strains. Probiotics used as adjuvant therapy help restore the homeostasis of the vaginal microbiome; however, due to inconsistent evidence, they are currently not included in treatment recommendations.